A multi‐technique approach for the characterization of decorative stones and non‐destructive method for the discrimination of similar rocks. (11th October 2013) - Barone, Germana; Crupi, Vincenza; Longo, Francesca; Majolino, Domenico; Mazzoleni, Paolo; Raneri, Simona; Venuti, Valentina
<x xml:space="preserve">Abstract</x> In this paper, a multi‐technique approach, at different scale of observation, is used to characterize a group of decorative stones and to permit to distinguish rocks with similar aspect but coming from different areas. In particular, the samples under study are sedimentary and metamorphic rocks, widely used as building blocks of modern and historical constructions and sculptures. The petrographic and mineralogical features of such rocks were performed by optical microscopy and Raman and Fourier transform infrared absorbance spectroscopies. These techniques permitted to obtain a complete structural, textural, and mineralogical characterization. At elemental level, the investigation was carried out by X‐ray fluorescence (XRF). In particular, XRF and Raman measurements were collected using portable instrumentations, whose advantages for the in situ analysis have been pointed out. The obtained results evidenced the high discriminant capability of the portable XRF for the decorative stones especially when this method is coupled with mineralogical and petrographic information. In this context, we propose to create a database for precious ornamental stones, which could be a starting point for a non‐destructive characterization, even useful for provenance study and/or certification of origin. Copyright © 2013 John Wiley & Sons, Ltd.